Evidence for Ecological Flexibility in the Cosmopolitan Genus Curtobacterium - Chase, Alexander B.; Arevalo, Philip; Polz, Martin F.; Berlemont, Renaud; Martiny, Jennifer B. H. (Frontiers in Microbiology, 2016)
Assigning ecological roles to bacterial taxa remains imperative to understanding how microbial communities will respond to changing environmental conditions. Here we analyze the genus Curtobacterium as it was found to be the most abundant taxon in a leaf litter community in southern California. Traditional characterization of this taxon predominantly associates it as the causal pathogen in the agricultural crops of dry beans. Therefore, we seek to conduct a broad investigation into this genus to ask whether its high abundance in our soil system is in accordance with its role as a plant pathogen or if alternative ecological roles are needed. By collating >24,000 16S rRNA sequences with 120 genomes across the Microbacteriaceae family, we show that Curtobacterium has a global distribution with a predominant presence in soil ecosystems globally. Moreover, this genus harbors a high diversity of genomic potential for the degradation of carbohydrates, specifically with regards to structural polysaccharides. We conclude that Curtobacterium may be responsible for the degradation of organic matter within litter communities.